The Effect of Fluid Overload Control Program on Knowledge and Behavior Among Caregivers of End-Stage Renal Disease Patients on Hemodialysis - Ummee, Kanyanat; Rerkkasem, Kittipan; Wungrath, Jukkrit (UI Scholars Hub, 2023)
End-stage renal disease (ESRD) is a pressing health issue, and patients on hemodialysis frequently grapple with fluid overload. In Chiang Mai, Thailand, from September to November 2022, this study was conducted to assess the impact of an educational program on the knowledge and behavior of caregivers managing fluid overload in ESRD patients. Using a quasi-intervention design, participants were categorized into two groups: the intervention group, which underwent the educational intervention, and the control group, which continued with standard care. The educational content was grounded in existing studiesand insights from healthcare professionals, caregivers, and patients. Post-intervention results revealed a significant enhancement in the knowledge andbehavior of caregivers in the intervention group regarding fluid overload control compared to the control group (p-value<0.05). This study emphasizes thepotential benefits of structured and evidence-based educational initiatives in equipping caregivers with the tools they need to better manage fluid balance, ultimately leading to improved patient outcomes.